Prevalence and severity of molar incisor hypomineralization in children aged 11-16 years of a city in Karnataka, Davangere - M Kirthiga; P Poornima; R Praveen; P Gayathri; M Manju; M Priya (Wolters Kluwer Medknow Publications, 2015)
Introduction: Molar incisor hypomineralization (MIH) describes the clinical picture of hypomineralization of systemic origin affecting one or more first permanent molar. There is a rarity of prevalence studies in Indian population. Objectives: The main aim of this study was to investigate the prevalence of MIH in a population of South Indian children. Settings and Design: A cross-sectional epidemiological survey, included 2000 children aged 11-16 years chosen by stratified random sampling from government and private schools of Davangere, a city in South India. Materials and Methods: Evaluation of MIH and decayed, missing and filled teeth was carried out in these children by a calibrated examiner. The severity of hypomineralization was recorded according to the Wetzel and Reckel scale. Statistical Analysis: Chi-square test was used to analyze the categorical data. P ≤ 0.05 was considered for statistical significance. Results: About 8.9% of all examined children showed at least one ill-structured first permanent molar in terms of MIH. The male and female ratio was found to be 1:1.1. The decreasing order of occurrence of MIH affected teeth were permanent maxillary molars, maxillaryincisors, mandibular molars and the mandibular incisors. Conclusion: The prevalence of MIH in the permanent dentition of south Indian children was 8.9%. There is a need for a proper planned preventive and restorative program with regard to the increasing prevalence of MIH.